KETEGANGAN ANTARA SYARIAT DAN NORMA SOSIAL DALAM PRAKTIK POLIGAMI: STUDI KUALITATIF ATAS PERSEPSI, STIGMA, DAN REPRESENTASI MEDIA - Nadia Putri; Aulia Rahmat (Islamic Family Law, STAI Sangatta Kutai Timur, 2025)
This study examines the tension between the religious legitimacy of Islamic sharia and contemporary social norms in the practice of polygamy in Indonesia. While polygamy is permitted in Islam under the fundamental condition of justice among wives, its practice frequently encounters social resistance rooted in values of gender equality and family integrity. Employing a descriptive qualitative approach, this research combines field studies and literature review methods. Data were collected through semi-structured interviews involving women in polygamous marriages, religious leaders, women’s rights activists, and members of the general public. The findings indicate that polygamy is predominantly perceived negatively by Indonesian society, largely due to prevailing social constructions, collective experiences associated with marital conflict, and biased representations in mass media. Women who become second wives often experience social stigma in the form of negative labeling and social exclusion, which adversely affects their psychological well-being and social standing. Moreover, mass media tends to reinforce narratives of injustice and conflict within polygamous households, producing a monolithic image that fails to capture the diversity of lived experiences. This study concludes that polygamy constitutes a complex and multidimensional social phenomenon that cannot be assessed solely on the basis of religious permissibility. Accordingly, a more equitable, contextual, and gender-sensitive approach is necessary for understanding and evaluating the practice of polygamy within Indonesian society.